Experience with in-action reviewing at points of entry. (20th October 2021) - de Rooij, D; van de Watering, M; van Dijk, R; Appels, R; Veenstra, T; Swaan, C; Timen, A
Abstract: Background: Lessons learned and experiences gained ask for enhancing the response even during a crisis. We present the application of the in-action review (IAR) of Dutch ports and airports, based on methods developed by the World Health Organization (WHO) and the European Centre for Disease Control (ECDC). Methods: We performed two separate IARs among Dutch airports (5/5) and ports (15/16) respectively. 1) A questionnaire among participants was used to decide upon most urgent matters to discuss during a 4-hour online meeting. 2) a 4-hour, interactive, online meeting was held among local representatives of points of entry, regional public health professionals, safety professionals, the national institute of public health and the ministry of health. Best practices, lessons, barriers and actions on different topics were first prepared in small groups, and discussed and finalized in plenary sessions. Follow-up of actions was performed during the consecutive 6 weeks at the moment of writing. A questionnaire among participants evaluated satisfaction and impact of the IAR among participants. Results: Main items for the online meetings were the implementation of measures, and regional and supra-regional collaboration. Most urgent actions formulated were a better integration of local needs into national policy making, and enhancing contacts among different points of entry. Implemented actions include the integration of local public health authorities involved at airports into an existing meeting structure at the national level; and an inter-port meeting structure that was developed leading to 3-weekly meetings to discuss upcoming challenges and exchange practices and advice. Conclusions: This is to our best knowledge the first time that an in-action review has been performed specifically for the point of entry setting. Performing IARs, online with operational partners led to quick wins and a better network during the COVID-19 pandemic.